Exploring Journalists’ Intentions Towards Digital Mobile Technologies: Extending the Technology Acceptance Model (TAM) in the Context of Ghana - Demuyakor, Dr. John; Boye-Doe, Zillah (Society & Sustainability, 2024)
In recent years, the use of digital mobile technologies for journalistic practice has gained much popularity among Ghanaian journalists. In this study, we explored three original Technology Acceptance Model (TAM) variables (perceived ease of use, perceived usefulness, and social influence) and two additional variables, (the cost of smartphones, and the cost of mobile data) to predict the relationship between the five variables, and journalists’ intention to use Digital Mobile Technologies (DMTs). A structured questionnaire was used to solicit data from 281 Ghanaian frontline journalists through an online survey. The respondents were selected by purposive sampling. Structural Equation Modelling analysis of the data showed that, as the cost of smartphones, and the cost of mobile data increases, journalists’ intention to use technology decreases in Ghana. Thus, mobile data and the cost of smartphones had a negative relationship with journalists’ intention to use DMTs. The testing of perceived ease of use, perceived usefulness, and social influence, however, reported a positive relationship with the use intention. The findings from this study have implications for policy change on the reduction of the prices of both mobile data and smartphones to enhance the use of DMTs among journalists in Ghana. Also, the findings from this study could be considered a template for the proper regulation of the use of DMTs for enhanced practice of journalism in Ghana and other developing countries.